Non-flammable Phosphate-Grafted Nanofiber Separator Enabling Stable-Cycling and High-Safety Lithium Metal Batteries. Issue 3 (10th March 2023) - Lin, Qiong; Wang, Zhongxin; Sun, Longfeng; Liu, Lingli; Song, Xuan; Li, Dongxia; Lin, Qixin; Xue, Yuxin; Sun, Xiangfeng; Gui, Xuefeng; Xu, Kai
Abstract : Lithium metal batteries (LMBs) are promising rechargeable energy storage devices with high energy densities and long lifetimes. Nevertheless, safety concerns constitute a severe impediment to the commercial demand for LMBs, including uncontrollable lithium dendrites, heat-intolerant separators, and flammable electrolytes. Herein, a novel separator (PSVHM) containing poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(methyl methacrylate) (PMMA) and cage silsesquioxanes, phosphorous-containing acrylate monomers is fabricated by electrospinning with in situ ultraviolet-irradiation grafting polymerization. Attributed to the presence of phosphate groups in the membrane with flame retardant properties, the PSVHM separators have outstanding self-extinguish capabilities. In addition, the 3D-crosslinked PSVHM separator possesses high ion conductivity, and excellent mechanical strength, thus suppressing the uneven lithium dendrites and constructing a stable solid electrolyte interface (SEI). Moreover, cell assembled with the PSVHM separator exhibits an ultra-capacity retention of 98% after 200 cycles at a high current density of 2 C. This work provides a guideline for the preparation of high-safety and high-performance lithium metal batteries.